Mental health crisis training for non-mental health professionals. Issue 4 (16th July 2020) - Maindonald, Rebecca; Attoe, Chris; Gasston-Hales, Melanie; Memon, Perah; Barley, Elizabeth
Abstract : Purpose: This study aims to evaluate a training in mental health crisis support for non-mental health professionals who work in urgent care settings. The training consists of an e-learning module, a one-day face-to-face (F2F) interactive study day and simulation training. Design/methodology/approach: This multi-methods study collected data pre and post training and at three to six months post training. Validated questionnaires, rating scales and open-ended questions were used to measure self-efficacy in health-care skills, attitudes towards mental illness and knowledge and confidence in working in mental health. A subsample of participants was interviewed post training about how they had used the knowledge and skills learned. Findings: A total of 706 staff completed the e-learning, 88 attended the F2F training and 203 attended simulation training. Overall satisfaction with the training was high, with F2F and simulation training preferred. Statistically significant improvements in self-efficacy for health-care skills, positive attitudes towards mental illness, and mental health-related knowledge and confidence were found post training. Qualitative analyses of interview and survey data indicated that participants had translated learning to practice through improved attitudes and behavioural changes when working with patients experiencing a mental health crisis. Originality/value: This training improved mental health-related knowledge, confidence and self-efficacy and reduced mental health-related stigma in professionals who provide urgent care to people in mental health crisis. Participants reported changes to their practice following training; this is important as care has been inadequate for this group. Workforce planners and leaders should consider implementing this or similar training widely.